Polemika Józefa Mehoffera z hrabią Karolem Lanckorońskim jako przedmiot refleksji estetycznej Berty Zuckerkandl (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The article presents the opinion of Berta Zuckerkandl, a Viennese journalist and art critic, about the dispute that arose between Józef Mehoffer, a painter, stained glass artist, graphic artist, representative of modernism around 1900, and Karol Lanckoroński. The basis is the publication Zuckerkandl Hat ein Kunst-Mäcen das Veto-Recht? [Does a patron of arts have a veto right?] published in the journal „Die Kunst für Alle: Malerei, Plastik, Graphik, Architektur” in 1903. The quoted text was translated from the language German into Polish. Karol Lancoroński wrote A bit about the works at Wawel, while Mehoffer replied in Remarks on art: Reply to the letter from count. Karol Lanckoroński on the restoration of the Wawel Cathedral. Zuckerkandl criticizes the patron and responds to the dispute. In the text, which is characteristic of the way of writing about the assessment of contemporary art by Zuckerkandl, which as an art critic many times supported the artists, it also included excerpts from the painter’s letter. The opinion-forming reviewer was interested in the dispute between the painter Józef Mehoffer and Count Karol Lanckoroński regarding the admissible forms of modern art introduced into the interiors of monuments, especially churches, in which she sided with Mehoffer. The author presents the views of Mehoffer, Lanckoroński and Zuckerkandl.